Feasibility of population screening tests to establish a healthy ageing trajectory. (January 2019) - Gordon, Susan J; Grimmer, Karen A; Baker, Nicky; Bell, Elaine; Coveney, John; Jordaan, Johanna H; Lind, Christopher; Marin, Tania; Murray, Joanne; Norton, Lynda H; Perimal-Lewis, Lua; Sparrow, Karen; et al.
Objectives: There are no agreed comprehensive tests for age-related changes to physical, emotional, mental and social functioning. Research into declining function focuses on those 75 years and older and little is known about age-related changes in younger people. The aims of this project were (1) to ascertain a comprehensive test battery that could underpin community-based health screening programmes for people aged 40–75 years and pilot both (2) community-based recruitment and (3) the utility, acceptability, response burden and logistics. Methods: A total of 11 databases were searched using a broad range of relevant terms. An identified comprehensive, recent, high-quality systematic review of screening instruments for detection of early functional decline for community-dwelling older people identified many relevant tools; however, not all body systems were addressed. Therefore, lower hierarchy papers identified in the rapid review were included and expert panel consultation was conducted before the final test battery was agreed. Broad networks were developed in one Australian city to aid pilot recruitment of community-dwellers 40–75 years. Recruitment and testing processes were validated using feasibility testing with 12 volunteers. Results: The test battery captured (1) online self-reports of demographics, health status, sleep quality, distress, diet, physical activity, oral health, frailty and continence; and (2) objective tests of anthropometry; mobility; lung function; dexterity; flexibility, strength and stability; hearing; balance; cognition and memory; foot sensation; and reaction time. Recruitment and testing processes were found to be feasible. Conclusion: This screening approach may provide new knowledge on healthy ageing in younger people.